Effect of temperature on the physiological characteristics of Awassi and crossbred sheep - Saeed, Osama Anwer; Abdulghafoor, Rawaa Turk; Al-Salmany, Sawsan Sabir; Ali, Faris Mahmoud; Samsudin, Anjas Asmara; Mahmood, Elham Khalifa (Malque Publishing, 2023)
This research was carried out to analyze the hematological, biochemical and physiological characteristics correlated with climate temperature in Awassi and crossbred sheep. Two hundred fifty adult Awassi and crossbred sheep (Arabi x Hamadani) were used. Three times weekly, ten times for each breed, vital signs, including heart rate (HR), respiratory rate (RR), rectal temperature (RT), and skin temperature (ST), were recorded. The heat tolerance indices (HT) and the heat tolerance coefficient (HTC) were evaluated. SAS was used to conduct the analyses, which included variance and correlation analyses. Awassi had a significantly higher (P < 0.01) RR than crossbred in the summer under low stress conditions. Awassi HR was significantly lower than that of crossbred sheep, which recorded the highest value in summer. There were no significant differences in RT, HT and HTC between Awassi and crossbred sheep. MCH, MCV, and RDW increased substantially in Awassi sheep exposed to colder winter temperatures. In summer, Awassi's liver enzyme and triglyceride levels significantly decreased, while albumin levels increased. Both HT and HTC had negative correlations with RR. Therefore, it can be concluded that the Awassi breed is equally adapted to the region's hot and arid climate.